Games and Physical Activity in the social educator’s pre-service training in Spain - Iván López Fernández; José Luis Chinchilla Mínguet (Revista Electrónica Interuniversitaria de Formación del Profesorado)
We analyze contents on games and physical activity within all curricula from Spanish universities offering the degree in Social Education during the academic year 2006-2007. The presence of related subjects in more than half of the curricula shows the interest given to this type of activities in social intervention. Nevertheless, the importance of physical and ludic activity in the social educator initial training is very varied as is dependent on the university and the learning itinerary chosen by the students.This article attempts to lay the foundations for the development of a shared proposal of initial training on games and physical activity for the social educator.